Collaboration of Resources in Task Force for Prevention and Handling Victims of Human Trafficking in Indonesia - Rahmat Hidayat; Syamsuddin Syamsuddin (Department of Government Studies Universitas Muhammadiyah Makassar, 2020)
The purpose of this study is to examine the cause of the ineffectiveness of resource collaboration in preventing and handling trafficking victims in West Java Province. This research method is a qualitative study that focuses on human and social problems through primary and secondary data collection. The results of this study indicate that the collaboration of resources in the prevention and handling of victims of trafficking in persons in West Java Province has not been effective. It triggered by the leading sector, problems of coordination of sharing resources, overlapping problems, roles, and resources, political factors, constraints of responsiveness of policymakers, and administrative issues.